Link aware unsolicited grant service packet scheduling for mobile WiMAX - Shu'Aibu, D. S. (IEEE, 2011)
Packet scheduling in wireless network is one of the issues that requires attention to quality of service provision (QoS). In heterogeneous wireless network, whereby many packets of different QoS are involved, packet scheduling becomes more difficult. This paper presents packet scheduling algorithm that uses earliest deadline first for scheduling constant bit rate packets. We estimate the wireless link based on the total path loss and obtain SNR value of the packet for scheduling. The simulation shows that the proposed algorithm has achieved higher throughput.